PENGARUH KECERDASAN EMOSIONAL, KECERDASAN INTELEKTUAL, KECERDASAN SPRITUAL DAN KOMITMEN ORGANISASI TERHADAP KINERJA AUDITOR - Hayatul Khairat; Yunieta Anisma; Rofika ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The aims of this study is to determine: 1. impact of emotional intelligent on auditor’s performance 2. impact of intellectual intelligent on auditor’s performance 3. impact of spiritual intelligent on auditor’s performance 4. impact of organizational commiment on auditor’s performance. This study was classified as causative study. The Population of this study were auditors on CPA firm.The sample are auditors on CPA firm in Padang, Pekanbar and Batam. The collection technique of this study was the technique of survey by distributing queationnaires directly to each auditors on CPA firm. Studies show that: 1. emotional intelligent had a significant positive impact on auditor performance 2. intellectual intelligence had a significant positive impact on auditor performance 3. spiritual intelligence had a significant positive impact on auditor performance. 4. Organizational commitment had a significant positive impact on auditor performance. 1. Sample of this study was limited to the auditors on CPA firm in Padang, Pekanbar and Batam. The result might be different if the sample were expanded. 2. the auditors on CPA firm should always pay attention to improve balance between emotional, intellectual, spiritual intelligence and also proffesional ethics to achieve more maximum performance.Keywords: auditors, emotional, intellectual, spiritual, organizational and commiment